Analysis of Current Tax, Deferred Tax, and Deferred Tax Assets on Earnings Management - Salim, Thomas; Yuniarwati, Yuniarwati (Syntax Corporation, 2024)
The goal of this study is to examine the impact of current taxes, deferred taxes, and deferred tax assets on earnings management. The research focuses on companies operating in the industrial sector listed on the Indonesia Stock Exchange during the years 2020, 2021, and 2022. A sample of 20 companies is selected using purposive sampling. Data processing involves multiple regression analysis assisted by Eviews 13 and Microsoft Excel. The findings indicate that current taxes have a significant positive impact on earnings management, while deferred taxes and deferred tax assets do not have a significant positive impact on earnings management. The implications of this research highlight the role of current taxes, deferred taxes, and deferred tax assets as detectors to track the movements of managers who have engaged in earnings management in the financial reports of companies, particularly in the income statement section.